Electrokinetic-potential fluctuations generated by jet impingement - Duckstein, Lucien, author; Cermak, J. E. (Jack E.), author; Colorado State University, Civil Engineering Section, publisher (Colorado State University. Libraries, 1962)
Electrokinetic-potential fluctuations produced by a two-dimensional submerged water jet impinging on a plate have been measured. The potential fluctuations are postulated to be linearly related to the three velocity fluctuation components u'x, u'y, uz'. In the particular case when u'x > u'y > u'z , the potential fluctuations are approximately proportional to the longitudinal-velocity fluctuations u'x. Normalized frequency distributions of potential-fluctuation measurements agree with velocity-fluctuation data taken by Klebanoff and Laufer with a hot-wire anemometer at a dimensionless distance y/o = 10 to -3 from the wall. The hypotheses made concerning the relationship between potential and velocity fluctuations give a possible explanation of the change in the shape of the potential-fluctuation spectrum with the flow velocity and the electrical conductivity of the water.
Electrokinetic potential fluctuations generated by jet impingement
CER62LD40.
June 1962.
Keywords: Kinetic theory of liquids; Jets -- Fluid dynamics; Surface chemistry